NUMERICAL SIMULATION OF ARMOURED FIGTHING VEHICLE SUBSYSTEM TO COMPLY WITH NATOÃâÃâs STANAG 4569 LEVEL III - - NIM: 23616031, RENI
Blast loading numerical simulation using subsystem scale of armoured fighting vehicle was carried out to increase its protection level from level 2 to 3 according to NATO’s STANAG 4569. The add on sandwich structure with aluminium foam core known as a good energy absorber is used for blast resistant structure to increase the resistancy of armoured fighting vehicle against blast. The configuration of V-shaped structure as an alternative way to managing the blast energy on structure was applied in this study. Numerical simulation was carried out to compare the resistance against blast among the floor subsystem with monolithic floor (single plate), flat shaped and V-shaped aluminium foam sandwich structure. The simple blast model based on empiric blast pressure distribution, CONWEP model and by modeling high explosive material as a continuum using Smoothed Particle Hydrodynamics (SPH) was used to model the explosion of high explosive material. Validation was done to show the ability of these models to represent the blast. Further, numerical simulation validation was carried out using experiment data from literature. Results showed that both flat dan V-shaped aluminium foam sandwich structure can resist blast load for level III of NATO’s STANAG 4569 and V-shaped aluminiun foam sandwich structure gave the best results in terms of maximum floor acceleration and displacement of armoured fighting vehicle without increasing the vehicle mass significantly.